CALCULATION ESTIMATION OF MAXIMUM CONTACT PRESSURES IN CYLINDRICAL METAL POLYMER SLIDING GUIDE WITH BUSHING MADE OF MOGLICE EPOXY COMPOSITE - Чернець, Мирон Васильович; Федорчук, Світлана Володимирівна; Корнієнко, Анатолій Олександрович; Іщенко, Анатолій Олексійович; Радіоненко, Олександр Васильович (Problems of Friction and Wear, 2021)
Using the developed method of research of contact pressures in cylindrical metal-polymer sliding guides their calculation was carried out for the antifriction polymer composite material Moglice of cold hardening on epoxy basis of Diamant company. The influence of load, bushing diameter and radial clearance on the maximum contact pressures in the cylindrical guide is investigated. Quantitative and qualitative regularities of their change from the accepted factors of influence are revealed: at increase of loading four times the maximum contact pressures and contact angles will increase twice irrespective of change of sizes of a radial clearance and diameter of a basis; an increase in its diameter leads to a directly proportional decrease in the maximum contact pressures; doubling the radial clearance leads to a 1.41-fold increase in pressure, regardless of changes in the magnitude of the load and the diameter of the base. Regularities of change of contact parameters from the specified factors are given graphically.